Receptor Interacting Protein Kinase Pathways Regulate Innate B Cell Developmental Checkpoints But Not Effector Function in Mice - Parthasarathy, Raksha; Hägglöf, Thomas; Hadley, Jason T.; McLennan, Alexandra; Mattke, Aiden; Dudley, Elizabeth A.; Kumagai, Abigail; Dong, Lily Q.; Leadbetter, Elizabeth A. (Frontiers in Immunology, 2021)
Mutations in the scaffolding domain of Receptor Interacting Protein kinases (RIP) underlie the recently described human autoimmune syndrome, CRIA, characterized by lymphadenopathy, splenomegaly, and autoantibody production. While disease mechanisms for CRIA remain undescribed, RIP kinases work together with caspase-8 to regulate cell death, which is critical for normal differentiation of many cell types. Here, we describe a key role for RIP1 in facilitating innate B cell differentiation and subsequent activation. By comparing RIP1, RIP3, and caspase-8 triple deficient and RIP3, caspase-8 double deficient mice, we identified selective contributions of RIP1 to an accumulation of murine splenic Marginal Zone (MZ) B cells and B1-b cells. We used mixed bone-marrow chimeras to determine that innate B cell commitment required B cell-intrinsic RIP1, RIP3, and caspase-8 sufficiency. RIP1 regulated MZ B cell differentiation rather than development and RIP1 mediates its innate immune effects independent of the RIP1 kinase domain. NP-KLH/alum and NP-Ficoll vaccination of mice doubly deficient in both caspase-8 and RIP3 or deficient in all three kinases (RIP3, caspase-8, and RIP1) revealed uniquely delayed T-dependent and T-independent IgG responses, abnormal splenic germinal center architecture, and reduced extrafollicular plasmablast formation compared to WT mice. Thus, RIP kinases and caspase-8 jointly orchestrate B cell fate and delayed effector function through a B cell-intrinsic mechanism.